Concepções e práticas pedagógicas em educação a distância: o caso do curso de administração a distância UAB-UEPB-2006-2010 - Barros, Maria das Graças (2011)
Distance Education (EaD) has been evolving to meet up with new social demands, and definite as a modality that uses today's most advanced technologies to promote interaction and interactivity to a view of learning among subjects set in a socio-historical context . The EaD's proposal is to insert the individual in the production process of knowledge networking, collaborative and collectively. There are several resources used for this purpose, since virtual platform aggregated with it's tools such as chat, forums, files, tasks, etc. to other artifacts that can be inserted on the process of teaching and learning as links, e-mails, blogs , twitter, etc.. The objective of this task was to investigate the theoretical concepts that implicitly or explicitly guides the teachers' pedagogical practices of the 6th semester of the class of Distance Administration of UEPB. To this, we identified the learning activities offered by teachers and their tools, focusing on the underlying concepts. Finally, we investigated, on the teachers words, the pedagogical concept that supports their practices. From the perspective of redefinition and reconstruction of knowledge is proposed to discuss the approach Vygotsky's social interactionism and the pedagogic concept of mediation as a reference for it evidenced a practice that fills the education requirements connected to the current needs of our society, so that the technologies are embedded in favor of constructing knowledge. The study is based on the perspectives of teaching and learning that are established in each paradigm, so that we can reflect on the actions and interactions of teachers, from that. The research constitutes a case study of qualitative character, since it seeks to describe and interpret the meanings of the words of teachers, establishing a link between the theoretical and the empirical analysis of documents, records represented here by the use of Virtual Environment Learning with their tools and Pedagogical Political Project of the course. The survey results indicate that the teachers surveyed do not have a defined pedagogical concept and its practices are still attached to traditional pedagogical conceptions. They work with digital technologies in distance education, but not on size or potential conferred upon them, much less as a means for the mediation.